(A) For x representing the cost of one of Tanya's items, her total purchase cost 5x. The cost of one of Tony's items is then (x-1.75) and the total of Tony's purchase is 6(x-1.75). The problem statement tells us these are equal values. Your equation is ...
... 5x = 6(x -1.75)
(B) Subtract 5x, simplify and add the opposite of the constant.
... 5x -5x = 6x -6·1.75 -5x
... 0 = x -10.50
... 10.50 = x
(C) 5x = 5·10.50 = 52.50
... 6(x -1.75) = 6·8.75 = 52.50 . . . . . the two purchases are the same value
(D) The individual cost of Tanya's iterms was $10.50. The individual cost of Tony's items was $8.75.
Answer:
Step-by-step explanation:
Multiplying x+6y=-3 with 2 so its equal to first eqn,
Eliminating,
2x + 3y = 3 (1)
2x +12y = -6 (2) (because subtracting)
------------------
-9y =9
∴y=-1
eq. y in 1
2x -3=3
2x=3+3
x=6/2
=3
Pls mark me brainliest
Answer:
156
Step-by-step explanation:
1 3/5 of an hour is 96 you get that by addind 60 mins with 36(3/5) then just add 60 mins
i believe this is right if you have any questions let me know
All i know is that if the radius of a circle is 4 feet, the the diameter is 8 feet. Sorry, I don't know the rest.
The equation is <span>f(x) = 2x5 - 9x4 + 12x3 - 12x2 + 10x - 3 = 0
remark:
the sum of coefficients is = 2-9+12-12+10-3=-7+7=0, so a=1 is a zero of f
f can be written as </span>f(x) = (x-1)Q(x), and f(x) / (x-1)= Q(x)
after euclid's division
Q(x) = 2x4 - 7x3 + 5x2 - 7x +3
so for finding the other roots, making Q(x) for product of factors is a must